ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LABA USAHA MIKRO BERBASIS EKONOMI KREATIF BIDANG FASHION DI KOTA DENPASAR - Elliezer Umbu Mila Ringu Langu; Anak Agung Ketut Ayuningsasi (Adisam Publisher, 2025)
Micro, small, and medium enterprises (MSMEs) play a strategic role in driving economic growth, including in the city of Denpasar. However, in practice, many micro-businesses in the fashion sector face obstacles such as limited capital, low utilisation of information technology (IT), and unstable customer numbers. The purpose of this study is to analyse the simultaneous and partial effects of capital, IT utilisation, and customer numbers on the profits of creative economy-based micro businesses in the fashion industry in Denpasar. This study uses a quantitative approach with an associative method. Data collection was conducted through a questionnaire with 100 respondents using accidental sampling. The data analysis technique used is multiple linear regression preceded by validity, reliability, and classical assumption tests. The results of the study indicate that all variables in this study simultaneously have a significant influence on micro business profit. Partially, the variables of capital, IT utilisation, and number of customers have a positive and significant influence on micro business profit.